Acylated Ghrelin is Protective Against 6-OHDA-induced Neurotoxicity by Regulating Autophagic Flux - He, Xin; Yuan, Wei; Liu, Fei; Feng, Juan; Guo, Yanxia (Frontiers in Pharmacology, 2021)
Parkinson’s disease (PD) is one of the most common neurodegenerative disorders, and our previous study revealed that autophagic flux dysfunction contributes to the neuron death in 6-OHDA-induced PD models. Acylated ghrelin is a neuropeptide that has a variety of actions in the central nervous system. In the current study, we aimed to investigate whether ghrelin is neuroprotective in 6-OHDA-induced rat model and SH-SY5Y cell model and whether it is related to autophagic flux regulation. We observed that ghrelin could effectively reduce apomorphine-induced contralateral rotation in 6-OHDA-induced PD rats, preserve the expression of tyrosine hydroxylase (TH) and increase the cell viability. It could upregulate the expression of autophagy related proteins like Atg7 and LC3-II and downregulate p62, and downregulate apoptosis related proteins like Bax and cleaved caspase 3. SH-SY5Y cells transfected with adenovirus Ad-mCherry-GFP-LC3B further revealed that ghrelin could relieve the autophagic flux dysfunction induced by 6-OHDA. Lysotracker staining showed that ghrelin could reverse the decrease in lysosomes induced by 6-OHDA and immunofluorescence staining revealed a reverse of TFEB level in SH-SY5Y cells. Blocking autophagy activation with 3-methyladenine (3-MA) in rats treated with ghrelin and 6-OHDA showed no notable change in apoptosis-related markers, while blocking autophagosome fusion with lysosomes with chloroquine could notably reverse the downregulation of bax/bcl-2 ratio and cleaved caspase 3 expression by ghrelin. Additionally, knockdown ATG7, the upstream regulator of autophagy, with siRNA could further decrease the number of apoptotic cells in SH-SY5Y cells exposed to 6-OHDA and treated with ghrelin, while knockdown TFEB, a key transcription factor for lysosome biosynthesis and function, with siRNA could completely abolish the anti-apoptosis effect of ghrelin. These data suggest that ghrelin is neuroprotective in 6-OHDA-induced PD models via improving autophagic flux dysfunction and restoration of TFEB level.